أثر ضغوط العمل على الشعور بالاغتراب الوظيفي - إبراهيم، عبدالسلام محمد (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2015)
تمثل ضغوط العمل عقبة تعيق الفرد عن القيام بعمله على أتم وجه، وبالتالي شعوره بالعجز واللامعيارية وبالعزلة في بيئة العمل، وبأن العمل لا معنى له. وزيادة ضغوط العمل عن الحد الذي يستطيع فيه الفرد التكيف والتعامل مع تلك الضغوط ينتج عنه آثار سلبية تؤثر على سلوك وأداء الفرد، واستمرار تلك الآثار يترتب عليه شعور الفرد بالاغتراب الوظيفي إن الآثار الناتجة عن ضغوط العمل سوء كانت إيجابية أو سلبية لها تأثير في العديد من الجوانب الإدارية في منظمات الأعمال، وينظر إلى ردود الأفعال والسلوك غير مرغوب فيه من مظاهر ارتفاع معدل الغياب، وكثرة الشكاوي، وأخطاء العمل المتكررة، وضعف الأداء، وغيرها من أنماط السلوك على أنها ذات علاقة بضغوط العمل نتيجة للعبء الزائد في العمل، أو العلاقات المتعددة، مما يتسبب في الشعور السريع بالإجهاد أو الإحباط والملل من العمل. ويعتبر الاغتراب الوظيفي من أهم العناصر التي تؤثر سلبا في إنتاجية وأداء الفرد والمنظمة، لذا يجب على المنظمة أن تعمل على حسن إدارة تلك المشكلة. والشعور بالاغتراب يأتي من مصادر مرتبطة بالعمل وطبيعته، أو من البيئة الخارجية التي تؤثر على الأفراد والمنظمات، أي أن تعرض الفرد لمصادر ضغوط العمل يؤدي إلى شعوره بالاغتراب الوظيفي.
Represent an obstacle hindering the pressures of work for the individual to do his job to the fullest, and therefore he felt helpless and non-standard and isolation in the work environment, and that the work does not make sense. And increasing work pressures, which can limit the individual to adapt and deal with these pressures result in negative effects, affect the behavior and performance of the individual, and that these impacts result in the individual's sense of alienation career. The effects resulting from the pressures of work were positive have an impact on many of the administrative aspects of the business organizations, and looks at the reactions and behavior undesirable manifestation of the high rate of absenteeism, frequent complaints, and work errors repeated, and poor performance, and other patterns of behavior they are related to work stress as a result of the burden of excess labor, or multiple relationships, resulting in the rapid feeling stress or frustration and boredom of work. The alienation of the most important functional elements that adversely affect the productivity and performance of the individual and the organization, so the organization should operate on the good management of the problem. and a sense of alienation comes from the sources and nature of work-related, I believe the external environment that affect individuals and organizations, that any individual's exposure to sources of pressure at work leads to feelings of alienation career.
Keywords: الإغتراب الوظيفي -- ضغوط العمل -- إدارة الموارد البشرية -- التنمية المهنية